Can You Get Hooked on Lip Balm? : Top Cosmetic Scientists Answer Your Questions about the Lotions, Potions and Other Beauty Products You Use Every Day. - Perry Romanowski (Harlequin Enterprises, Ltd., 2012)
eBook : Document : EnglishView all editions and formats Summary: Why does my shampoo stop working? Are my cosmetics poisoning me? What does hypoallergenic mean? Are organic products better?Every day thousands of people turn to the scientists at the popular blog thebeautybrains.com for answers to their most pressing beauty questions. In The Beauty Aisle Insider you'll discover that:- Salon products are not necessarily better than products you can buy in the store.- Some of the